CO2 capture and utilization by KOH absorption and CaCO3 granulation in the fluidized-bed reactor - Sioson, Arianne Sebron; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
In order to reduce the carbon dioxide (CO2) emissions from Industries, innovations must be continuously be explored, that could efficiently reduce significant amount of CO2 emissions and make a useful new product from captured CO2 gas. In this study, a system was proposed for CO2 gas capture through KOH absorption and subsequent CaCO3 granulation. Potassium hydroxide (KOH) solution as CO2 gas absorbent is used due to its high absorption capacity. The use of fluidized-bed reactor (FBR) to granulate calcium carbonate (CaCO3) through the homogeneous granulation process could produce high purity, less moisture content and bigger size granules. Precipitation of CaCO3 exhibits high industrial demand due to its wider application and importance. The parameters varied by means of parametric experiment were operating pH (pHoperating), calcium-is-to-carbonate molar ratio ([Ca2+]/[CO32-]), concentration ([CO3?"Jin) and total influx flow rate (QT). The CaCO3 granules produced were collected, dried, sieved and analyzed for the evaluation of their physical and chemical characteristics through SEM, XRD and EDX analyses. The optimum operating condition was found to be at OpH of 10±0.2, [Ca2+)/(CO32-] of 1.50, [CO32-]in of 12 mM and Qt of 60 mL/min; with highest carbonate removal efficiency and carbonate granulation efficiency, were 97.8% and 95.9% respectively. This condition also produced CaCO3- aragonite granules of 1-2 mm diameter size, with amorphous surface and high purity.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Carbon dioxide mitigation; Calcium carbonate; Granulation